Two sides of a coin: ecological and chronobiological perspectives of timing in the wild. (9th October 2017) - Helm, Barbara; Visser, Marcel E.; Schwartz, William; Kronfeld-Schor, Noga; Gerkema, Menno; Piersma, Theunis; Bloch, Guy
Abstract : Most processes within organisms, and most interactions between organisms and their environment, have distinct time profiles. The temporal coordination of such processes is crucial across levels of biological organization, but disciplines differ widely in their approaches to study timing. Such differences are accentuated between ecologists, who are centrally concerned with a holistic view of an organism in relation to its external environment, and chronobiologists, who emphasize internal timekeeping within an organism and the mechanisms of its adjustment to the environment. We argue that ecological and chronobiological perspectives are complementary, and that studies at the intersection will enable both fields to jointly overcome obstacles that currently hinder progress. However, to achieve this integration, we first have to cross some conceptual barriers, clarifying prohibitively inaccessible terminologies. We critically assess main assumptions and concepts in either field, as well as their common interests. Both approaches intersect in their need to understand the extent and regulation of temporal plasticity, and in the concept of 'chronotype', i.e. the characteristic temporal properties of individuals which are the targets of natural and sexual selection. We then highlight promising developments, point out open questions, acknowledge difficulties and propose directions for further integration of ecological and chronobiological perspectives through Wild Clock research. This article is part of the themed issue 'Wild Clocks: integrating chronobiology and ecology to understand timekeeping in free-living animals'.